Pathways to Empowerment: Case Studies of Positive Deviances in Gender Relations in Ethiopia - Kinati, Wole; Temple, Elizabeth C.; Baker, A. Derek; Najjar, Dina (Springer, 2023)
Development eforts have increased women’s perceived empowerment and free dom, yet have failed to sustainably alter gender norms. There is a lack of research investigating reasons for this anomaly. This study, departing from the conventional approach, tries to fll this gap by employing an interpretative phenomenological approach to assess how women have managed to achieve expanded agency while living within a constraining normative environment. We argue that women have the capacity to deviate and the intentions that lead to new behaviors emerge not only from individuals’ attitudes, subjective norms, and perceived behavioral con trol, as suggested by the Theory of Planned Behavior, but also in combination with demographic and economic factors. Individuals need to make decisions in three ar eas ―self-conviction (attitude and perceived behavioral control), subjective norms (within household and community), and structures (state and non-state institutions). The results shed light on alternative empowerment pathways that could potentially inform the design of transformational interventions.